SEGURANÇA DO PACIENTE EM UNIDADES CIRÚRGICAS - Guilherme do Carmo Silva; Larissa Mota Oliveira; Horácio Pires Medeiros; Alcinês da Silva Sousa Júnior; Andrea das Graças Ferreira Frazão; Silvia Ferreira Nunes (REVISTA DE ESTUDOS INTERDISCIPLINARES, 2026)
Patient safety constitutes one of the main pillars of quality in healthcare assistance and is associated with the reduction of preventable harm during care. In surgical units, this issue becomes even more relevant due to the complexity of procedures and the high risk of adverse events, requiring educational strategies that involve patients, caregivers, and/or family members. In this context, educational websites emerge as digital tools capable of expanding access to information, improving understanding of health guidance, and promoting safer practices. This study aimed to analyze the available scientific evidence on the use of educational websites in promoting patient safety in surgical contexts, with emphasis on guiding family members in healthcare. This is an integrative literature review conducted in the databases BVS, SciELO, PubMed, and Google Scholar, considering studies published between 2023 and 2026. The results indicate that digital technologies significantly contribute to patient safety by standardizing information, reducing care failures, and strengthening health education. Furthermore, evidence shows that websites and other interactive technologies favor continuity of care, especially in the post-discharge period, increasing the autonomy of patients and family members. It was also observed that user empowerment is directly related to access to information and active participation in care. It is concluded that educational websites represent a promising strategy for promoting patient safety, especially in surgical units, by integrating accessible information, health education, and family participation in the care process.